2004
DOI: 10.1001/archneur.61.4.525
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Sleep Disturbances and Fatigue in Multiple Sclerosis

Abstract: There is a significant correlation between fatigue in MS patients and disrupted sleep or abnormal sleep cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
120
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 185 publications
(135 citation statements)
references
References 24 publications
10
120
2
3
Order By: Relevance
“…1 Third, abnormalities of circadian rhythm, including, in particular, increased daytime somnolence, have recently been described in other fatigue-associated conditions and implicated heavily in the pathogenesis of fatigue. 9,10 The data presented here confirm the presence of significant sleep abnormality in PBC, highlight a particular increase in daytime somnolence, and suggest that the degree of such daytime somnolence correlates significantly with severity of perceived fatigue.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…1 Third, abnormalities of circadian rhythm, including, in particular, increased daytime somnolence, have recently been described in other fatigue-associated conditions and implicated heavily in the pathogenesis of fatigue. 9,10 The data presented here confirm the presence of significant sleep abnormality in PBC, highlight a particular increase in daytime somnolence, and suggest that the degree of such daytime somnolence correlates significantly with severity of perceived fatigue.…”
Section: Discussionsupporting
confidence: 75%
“…Comparisons were made between groups using Student t test (for normally distributed data sets) and Mann-Whitney non-parametric testing for nonnormally distributed data sets. [5][6][7][8][9], P Ͻ .05). Global sleep quality as assessed by the PSQI was significantly lower in the patient group than in the normal controls (Table 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Sleepiness and fatigue, although often occurring in the same patient, can exist independently, and either can negatively impact quality of life in MS. 3 The etiology of these symptoms has not been completely elucidated, although studies have shown that sleep disturbances are associated with a higher incidence of fatigue and daytime sleepiness. [6][7][8] Obstructive sleep apnea, often associated with sleepiness or fatigue, is prevalent in MS. 9,10 Other non-therapy-related diagnoses that may affect the efficiency of sleep could include sleep fragmentation, restless leg syndrome/periodic limb movements of sleep, menopause, frequent urination, muscle spasms, depression, and pain.…”
mentioning
confidence: 99%
“…Unfortunately, many neurologists exhibit a therapeutic nihilism towards this debilitating symptom in regarding fatigue as some immanent and intractable feature of the condition with which the patient "has to learn to live". Only in recent years, a possible association of daytime fatigue with sleep disorders has become into focus; however, only very few studies have attempted to investigate the relationship between sleep disorders in general and MS-related fatigue by PSG or accelerometry and not only by questionnaires on sleep quality [14][15][16][17]. In sum, it is undoubtful that sleep disorders can contribute to daytime fatigue in MS.…”
mentioning
confidence: 99%